Åkertistel : biologi och icke-kemisk bekämpning - Nordenhäll, Sara (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
A growing problem in Swedish herbicide free agriculture, the Canadian thistle has been the object of several new trials, seeking methods for non-chemical weed control. The new trials have mainly confirmed earlier experiences; that the most successful methods of control are springtime ploughing, repeated cutting and competition from a stout crop. Row hoeing has also been proven effective. As opposed to earlier recommendations, half season fallow has shown to be a risky and often ineffective method of control. Trials regarding biological methods have shown that above others thistle rust (Puccinia punctiformis) may have the potential of controlling Canadian thistle the future.